Evaluation of Indian diabetes risk score and random blood sugar testing for opportunistic screening of type 2 diabetes patients at a district hospital of Gujarat - Nilesh Chandrakant Fichadiya; Ammiruddin M Kadri; Bhargav B Dave (Wolters Kluwer Medknow Publications, 2022)
Background: India is home to 69.2 million diabetics. For opportunistic screening of type 2 diabetes mellitus (DM), random capillary blood sugar (RBS) testing is used. Another method is Indian Diabetes Risk Score (IDRS), which is a simple and cost effective method for opportunistic screening of type 2 DM patients. The aim is to evaluate the screening test parameters of RBS testing and IDRS for opportunistic screening of undiagnosed type 2 DM patients. Materials and Methods: A cross-sectional study was done during February 2017 to August 2017 at a district hospital of Western Gujarat. A sample size of 317 patients was calculated using Buderer's formula. Systematic random sampling was used and every third patient was selected from the general Outpatient Department(OPD) attendees of 30 years or more. MS Excel and Epi Info v7.2 was used for statistical analysis. Screening parameters and accuracy of IDRS and RBS were calculated taking result of the oral glucose tolerance test as clinical reference. Results: The mean age of study participants was 50.9 (SD 12.17) years with 44.2% males and 55.8% females. Sensitivity and specificity of RBS was 72.4% and 69.1%. Sensitivity and specificity of IDRS was 93.1% and 29.0%. On simultaneous (parallel) screening by IDRS and RBS, sensitivity was 98.3% and specificity was 23.2%. In sequential screening, where IDRS was used followed by RBS, sensitivity was 67.2% and specificity was 74.9%. Conclusions: This study has found that sequential screening using a simple diabetes risk score like IDRS followed by RBS is having higher accuracy and reduced cost of opportunistic screening of type 2 diabetes. Adopting sequential screening using IDRS as first step of screening followed by RBS in those found as high risk by IDRS is recommended.